2007
DOI: 10.1093/humrep/dem085
|View full text |Cite
|
Sign up to set email alerts
|

Xenotransplantation of testicular tissue into nude mice can be used for detecting leukemic cell contamination

Abstract: Grafting testicular tissue contaminated with leukemic cells led to tumor growth at the injection site without potential to differentiate germline stem cells into gametes. Xenografting could provide a novel functional strategy for simultaneous detection of malignant cell contamination and spermatogonial potential in testicular xenografts collected for fertility preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…13 Currently, this model is probably the most sensitive to detect the presence of viable malignant cells in frozen/thawed human ovarian tissue although using immunodeficient mice as a bioincubator for the development of leukemia cells may have some drawbacks. The transmission of rat leukemia requires very few malignant cells , 26,27 but it is less clear how many human cells are needed to introduce leukemia in mice 28,29 and it also depends on the mouse strain. 30 The administration route affects the take rate and Imamura et al found a higher take rate for human leukemic cell lines after subcutaneous inoculation as performed in the present study compared with intraperitoneal inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…13 Currently, this model is probably the most sensitive to detect the presence of viable malignant cells in frozen/thawed human ovarian tissue although using immunodeficient mice as a bioincubator for the development of leukemia cells may have some drawbacks. The transmission of rat leukemia requires very few malignant cells , 26,27 but it is less clear how many human cells are needed to introduce leukemia in mice 28,29 and it also depends on the mouse strain. 30 The administration route affects the take rate and Imamura et al found a higher take rate for human leukemic cell lines after subcutaneous inoculation as performed in the present study compared with intraperitoneal inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the poor specificity of spermatogonial surface markers, aggregation of germ and leukemic cells, and significant variations in the expression of specific leukemic surface markers were found to seriously limit the efficacy of both positive selection of normal testicular cells and deletion of leukemic testicular cells by FACS. Future development of functional deletion of malignancy, i.e., by culturing in vitro or xenotransplantation into an intermediate host (Hou et al 2007a), may provide new tools to guarantee the absence of tumor cells from clinical samples of testicular cells. The present investigation helps provide a platform for planning such future studies.…”
Section: Hou and Othersmentioning
confidence: 99%
“…Transmission of leukemia and isolation of leukemic lymphoblasts (from lymph nodes and blood) and testicular cells were performed as described previously (Jahnukainen et al 2001, Hou et al 2007a. A total of 40 terminally leukemic PVG rats 40 days of age (with transmission of leukemia occurring when they were 25 days old) and 3 age-matched, nonleukemic rats served as donors of lymphoblasts, testicular cells, and/or testicular sections (stored frozen; see below).…”
Section: Transmission Of T-cell Leukemia and Preparation Of The Cellsmentioning
confidence: 99%
“…The potential of using SSCs to preserve and restore fertility in patients receiving gonadotoxic therapies has been extensively discussed (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). In theory, testicular cells obtained via biopsy prior to cancer treatment could be cryopreserved and then retransplanted following clinical remission.…”
Section: Introductionmentioning
confidence: 99%